Complementary Possibilities in Human-Nature Interaction in An Urban Context – A Case Study: Darband River-Valley in Tehran (European Journal of Engineering Science and Technology, 2019)
One of the current key challenges concerning a city’s natural structures is to identify how the potential and existing methods of human-nature interaction can complement each other in a way that results in achieving sustainability in the full sense of the concept. In other words, it is necessary to define a subtle and nuanced set of complementary possibilities between human beings and nature while investigating metropolitan landscape structures. To this end, this paper aims to elaborate on the natural structures of the river-valleys of Tehran with specific consideration of one river-valley called Darband. With a length of 33km through the urban and peri-urban areas of Tehran from the northernmost to the southernmost points, Darband river-valley provides a wide range of potentials – as well as problems – in terms of human-nature interaction in its neighborhoods. This spectrum of potential includes mainly: inner-city local and medium-sized parks and the tendency for neighborhood-scale communication; urban spaces of squares and streets and the disappearing history; big parks and unconstructed pieces of land and social attitudes associated with specific days; mountainous recreational areas; and bridges as landscape in transit as well as acting as pause points. In this design- and context-based research, the applied methodology consists of a review of the related literature, direct observation, interviews, and design and planning. In this paper, the focus is primarily on socio-cultural aspects of sustainability, and the environmental aspect is studied as an affiliated and interdependent aspect.